Determinants of satisfaction with the detection process of autism in Europe: Results from the ASDEU study. (November 2022) - Guillon, Quentin; Baduel, Sophie; Bejarano-Martín, Álvaro; Canal-Bedia, Ricardo; MagÁn-Maganto, María; FernÁndez-Álvarez, Clara; Martín-Cilleros, María Victoria; SÁnchez-Gómez, María Cruz; García-Primo, Patricia; Rose-Sweeney, Mary; Boilson, Andrew; LinertovÁ, Renata; et al.
Satisfaction with the detection process of autism and its determinants was investigated using data from the Autism Spectrum Disorder in the European Union (2015–2018) network. A total of 1342 family members, including 1278 parents, completed an online survey collecting information about their experience and satisfaction with the early detection of autism in their child. Overall, the level of satisfaction varied considerably from one respondent to another. Difficulty in finding information about detection services, lack of professional guidance and support in response to first concerns, finding a diagnostic service on one's own, and a delay of more than 4 months between the confirmation of concerns and the first appointment with a specialist were all experiences individually associated with greater odds of being less satisfied. Using a dominance analysis approach, we further identified professional guidance and support in response to first concerns as the most important predictor of the level of satisfaction. These findings highlight the aspects of the process that need to be improved to enhance the experience of the detection process and are therefore relevant to guide health administrations toward actions to be implemented to this effect. Lay abstract: Professional guidance and support in response to first concerns appears to be an important predictor of the level of satisfaction with the detection process of autism in young children. In this study, we analyzed the views of 1342 family members, including 1278 parents, who completed an online survey form collecting information about their experience and satisfaction with the early detection of autism in their child. Specifically, we were interested in how specific experiences with the detection process relate to the satisfaction with it and whether we could identify important predictors of satisfaction. The detection process is an emotionally charged period for parents, often described as painful, chaotic, and lengthy. A better understanding of their experiences is important to take appropriate action to improve the detection process. In our sample, the level of satisfaction with the detection process varied greatly from one respondent to another. Among the different experiences we considered, whether or not respondents received professional guidance and support in response to first concerns explained most of this variation. We also found that difficulty finding information about detection services, lack of professional guidance and support in response to first concerns, having to find a diagnostic service on one's own, and longer delays between confirmation of concerns and first appointment with a specialist were experiences associated with a greater likelihood of being unsatisfied. The findings of this study highlight the importance of the parent–professional relationship in the detection process and have important practical implications for health administrations to improve the detection process.